2008
DOI: 10.1007/s10875-008-9252-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Serum HMGB-1 and sRAGE Levels in Systemic Sclerosis: Association with Disease Severity

Abstract: The high mobility group box 1 protein (HMGB-1)/adcanced glycation end products (RAGE) system is recently shown to play an important part in immune/inflammatory disorders. However, the association of this system in systemic sclerosis (SSc) remains unknown. To determine clinical association of serum levels of HMGB-1 and soluble RAGE (sRAGE) in patients with SSc, sera from 70 patients with SSc and 25 healthy controls were examined by enzyme-linked immunosorbent assay. Sera from Tight-skin mice and bleomycin-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
96
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 110 publications
(105 citation statements)
references
References 55 publications
7
96
0
2
Order By: Relevance
“…Innate immune signaling-mediated fibroblast activation was recently reported in SSc and its animal models. In SSc, serum levels and dermal expression levels of endogenous TLR4 ligands, such as HMGB1, hyaluronan, and fibronectin extra domain, are elevated (5,6,8,9). In in vitro experiments, TLR4 signaling induced by these candidate ligands results in fibroblast activation (5,6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Innate immune signaling-mediated fibroblast activation was recently reported in SSc and its animal models. In SSc, serum levels and dermal expression levels of endogenous TLR4 ligands, such as HMGB1, hyaluronan, and fibronectin extra domain, are elevated (5,6,8,9). In in vitro experiments, TLR4 signaling induced by these candidate ligands results in fibroblast activation (5,6).…”
Section: Discussionmentioning
confidence: 99%
“…It also was shown that dermal and lung fibrosis is attenuated in bleomycin (BLM)-treated TLR4-deficient mice (7). Endogenous potential TLR4 ligands are up-regulated in SSc lesional skin (5-7), and serum levels correlate with severe organ involvement and immunological abnormalities (8,9). Therefore, the TLR4 signaling pathway is suspected to play a central role in the SSc pathogenesis.…”
mentioning
confidence: 99%
“…Finally, HMGB1-DNA complexes induce cytokine secretion from mesangial cells in vitro (92). Serum HMGB1 levels are higher in patients with scleroderma and correlate with skin fibrosis and impaired lung function (93). The association with fibrosis is not restricted to autoimmune disorders, given that elevated levels of HMGB1 occur in patients with idiopathic pulmonary fibrosis (IPF) (94).…”
Section: Hmgb1 In Chronic Inflammatory and Autoimmune Diseasesmentioning
confidence: 99%
“…130,131 RAGE is implicated in the development of lung fibrosis 132 and its expression on the fibroblast cell surface has been correlated with SSc severity. 133 TLR4 signaling has been found to induce fibroblast proliferation 134 and the activation of plasmocytoid DCs. 114 Notably, TLR4 inhibition hindered the fibrotic process in a model of LPS-induced lung fibrosis.…”
Section: Systemic Sclerosismentioning
confidence: 99%